Da lógica global à valorização local - transformações econômicas e sociais na vida da população rural: um estudo exploratório na região sul do estado de Minas Gerias - Roque Filho, Mário Pereira (2011)
This work has as its main objective to investigate the social and economical transformations in a South city of Minas Gerais. In this research the agriculture of strawberry production has been selected because it is an important activity in the local context. This kind of strawberry production involves public politics of work organization and trade and it is significant in the country food politics. The thesis has focused on the complexity organization of work and trade developed by the farmers in the city of Tocós do Moji. It has been investigated, among other aspects, the particularities of strawberry production and trade, the technical innovations in the production, the revaluation of social and traditional practices in the rural area and the increase risks to the small farmer. In wider scenery of improvised work relations the reflection has been concentrated in the ways of work organizations and their reflections of the way of people‟s living. These people can be direct or indirectly involved with the strawberry culture which can focus on the production or the economical results. The specific intention of this research was to investigate the consequences and challenges in the peoples‟ way of living. The investigation result has confirmed our hypothesis. It is possible that an agricultural culture changes the economical and social life of the people if there is synergy, political will and involved actors‟ organization